Seasonal influenza vaccination among people with diabetes: influence of patients' characteristics and healthcare use on behavioral changes - A. Bocquier; S. Cortaredona; L. Fressard; F. Galtier; P. Verger (Taylor & Francis Group, 2020)
Annual seasonal influenza vaccination (SIV) is recommended for people with diabetes, but vaccine coverage remains low. We estimated the probabilities of stopping or starting SIV, their correlates, and the expected time spent in the vaccinated state over 10 seasons for different patient profiles. We set up a retrospective cohort study of patients with diabetes in 2006 (n = 16,026), identified in a representative sample of beneficiaries of the French National Health Insurance Fund. We followed them up over 10 seasons (2005/06-2015/16). We used a Markov model to estimate transition probabilities and a proportional hazards model to study covariates. Between two consecutive seasons, the probabilities of starting (0.17) or stopping (0.09) SIV were lower than those of remaining vaccinated (0.91) or unvaccinated (0.83). Men, older patients, those with type 1 diabetes, treated diabetes or more comorbidities, frequent contacts with doctors, and with any hospital stay for diabetes or influenza during the last year were more likely to start and/or less likely to stop SIV. The mean expected number of seasons with SIV uptake over 10 seasons (range: 2.6-7.9) was lowest for women <65 years with untreated diabetes and highest for men ≥65 years with type 1 diabetes. Contacts with doctors and some clinical events may play a key role in SIV adoption. Healthcare workers have a crucial role in reducing missed opportunities for SIV. The existence of empirical patient profiles with different patterns of SIV uptake should encourage their use of tailored educational approaches about SIV to address patients' vaccine hesitancy.